CTL escape - Progress in identifying therapeutic avenues to control HIV viraemia - Goulder, P (2000)
The central role of HIV-specific cellular immunity in controlling HIV replication is now established. Knowledge of how the virus in the majority of infected persons successfully evades these immune responses is critical to vaccine design. Virus escape from recognition by HIV-specific cytotoxic T-lymphocyte (CTL) responses has been a contentious issue for almost a decade, but recent data from the SIV macaque model of HIV infection suggest that CTL escape is a major factor in AIDS pathogenesis. This review describes the challenges to investigating CTL escape in HIV infection, and discusses the implications of recent studies in macaques and humans to improving our understanding of how effective immune-mediated control of HIV may ultimately be achieved. © 2000 Ashley Publications Ltd.